Introduction to the Study of European Immigration to Peru - Bonfiglio, Giovanni (1986)
In this paper the author intends to give an overview of the European immigration In Peru aiming for a first balance of the studies about the subject. Starting from a review of the most important censal sources of the XIX and XX centuries, he tries to answer the following questions about immigrants: which were their insertion strategies in the Peruvian society? To which type of economic activities were dedicated those who decided to stay in the country? The author's analysis concludes, among other things, that the European immigrants in Peru were not an homogenous group and besides, that the majority of them carne on their own initiative in spite of the favorable immigration policies issued by the different republican governments.